Functional polymorphisms of the TLR7 and TLR8 genes contribute to Mycobacterium tuberculosis infection. (May 2016) - Lai, Yung-Fa; Lin, Tsun-Mei; Wang, Chiou-Huey; Su, Pei-Yi; Wu, Jiun-Ting; Lin, Meng-Chih; Eng, Hock-Liew
Summary: Tuberculosis (TB) has recently re-emerged as a major global public health threat and Mycobacterium tuberculosis ( MTB ) is a highly successful pathogen that evolved remarkable strategies to establish persistent infection. There is strong evidence that host genetic factors influence individual susceptibility to TB. In this study, we evaluated the associations between the TLR7 and TLR8 genetic polymorphisms and TB susceptibility in Chinese individuals. The results demonstrated that the frequency of the TLR8 -129C allele was higher in male patients with pulmonary TB than in healthy controls (22.9% vs. 6.8%, p < 0.001). Based on haplotype analysis, the frequency of the TLR7 IVS2-151A/ TLR8 -129C haplotype increased the risk for TB infection compared to the wild-type allele ( TLR7 IVS2-151A/ TLR8 -129G), with OR = 3.23 (95% CI = 1.58–6.61; p = 0.001). An ex vivo phagocytosis assay that examined the functional effects of these polymorphisms on the defense against MTB revealed higher phagocytosis in monocytes from males with the TLR7 IVS2-151A/ TLR8 -129C genotype than in those with the wild-type allele (73.0 ± 20.3% versus 34.6 ± 8.1%; p  = 0.03). In addition, mRNA expression and cytokine production were analyzed in the whole blood of male healthy volunteers stimulated with inactivated MTB ex vivo . TNFα production was lower in TLR7 IVS2-151A/TLR8 -129C subjects than in those with the wild-type allele (578.4 ± 90.3 pg/ml versus 1043 ± 136 pg/ml; p  = 0.03), and the expression of TLR7 was significantly impaired (0.8 ± 0.1 folds, p  = 0.05) after MTB stimulation. In conclusion, these findings provide evidence that TLR7 and TLR8 genetic polymorphisms are associated with susceptibility to MTB infection, and the link is shaped by less effective MTB phagocytosis and impaired TLR signaling.